PENDAMPINGAN PENYUSUNAN PELAPORAN KEUANGAN PADA KELOMPOK USAHA KECIL DAN MENENGAH BROSEM SEMERU - Gina Harventy; Siti Zubaidah; Masiyah Kholmi (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2020)
Financial statements are a means used by companies to communicate their activities and performance to stakeholders. Such is the case with UMKM Brosem. Financial reports are also prepared as a form of accountability of fund managers to "stakeholders. Among other groups of SMEs who are members of the UMKM Brosem and the government in the aspect of taxation. This community service activity is expected to provide benefits and provide outputs that can be sustained for the management of Brosem, especially in the aspects of preparing financial statements. So that managers can compile financial reports according to standards, tax calculations in accordance with tax provisions, as well as the determination of the cost of production that is accurate as a basis for determining the selling price. If the financial statements can be prepared properly, it is expected to be able to realize transparent and accountable governance. Based on observations and interviews agreed with the service program partners focused on solving problems related to the preparation of financial statements. Therefore it is necessary to assist in the preparation of financial reports in accordance with EMKM financial reporting standards. KEYWORDS: Brosem Semeru; SAK EMKM; UMKM.